Selective separation of CO2–CH4 mixed gases via magnesium aminoethylphosphonate nanoparticles. Issue 15 (1st February 2016) - Simonato, Sara; Möllmer, Jens; Lange, Marcus; Gläser, Roger; Staudt, Reiner; Feldmann, Claus
Abstract : Magnesium 2-aminoethylphosphonate (Mg2 O(2AEP) × 4H2 O) nanoparticles (particle diameter: 20–30 nm; specific surface area: 360 m 2 g −1 ) are presented for selective separation of CO2 and CH4 . Abstract : Magnesium 2-aminoethylphosphonate (Mg2 O(2AEP) × 4H2 O) nanoparticles (particle diameter: 20–30 nm; specific surface area: 360 m 2 g −1 ) are presented for selective separation of CO2 and CH4 . Due to the base amino function, the nanoparticles can reversibly absorb CO2 with a maximal uptake of 153 mg g −1 . Absorption and desorption are studied by infrared spectroscopy as well as by gravimetric sorption analysis. Furthermore, Mg2 O(2AEP) × 4H2 O shows reversible selective separation of CO2 from CH4 . Here, pure and mixed gas adsorption isotherms (25 °C, 25 bar) of CO2 and CH4 show maximal uptakes of 153 mg g −1 (CO2 ) and 15 mg g −1 (CH4 ). Especially, data of mixed gas isotherms are comparably rare, but highly relevant for material characterization. Experimental isotherms were fitted by a dual-site Langmuir isotherm model (CO2 ) and a Tòth model (CH4 ). Mixed adsorption isotherms were modelled by volumetric-chromatographic methods resulting in a selectivity of α = 8 to 20.